(Pro)renin receptor and V-ATPase: from Drosophila to humans. - Rousselle, A.; Sihn, G.; Rotteveel, M.; Bader, M. (Clinical Science, 2014)
A decade ago, the (P)RR [(pro)renin receptor] was discovered and depicted as a potential activator of the tissue renin-angiotensin system. For this reason, the role of the (P)RR in cardiovascular diseases and diabetes has been particularly studied. However, the discovery of embryonic lethality after (P)RR gene deletion in mouse and zebrafish paved the way for additional roles of (P)RR in cell homoeostasis. Indeed, the (P)RR has been shown to associate with vacuolar H+-ATPase, hence its other name ATP6ap2. Developmental studies in Xenopus and Drosophila have revealed an essential role of this association to promote the canonical and non-canonical Wnt signalling pathways, whereas studies with tissue-specific gene deletion have pointed out a role in autophagy. The present review aims to summarize recent findings on the cellular functions of (P)RR emerging from various mutated and transgenic animal models.